Social network analysis of construction companies operating in international markets: case of Turkish contractors - Akgul, Bartug Kemal; Ozorhon, Beliz; Dikmen, Irem; Birgonul, M. Talat (Journal of Civil Engineering and Management, 2017)
Investigation of market entry strategies is critical for the success of international contractors. Establishing partnerships is among the most effective vehicles of operating in international markets. The major objective of this paper is to analyze the partnership behavior of contractors in overseas projects. In this respect, social network analysis (SNA) was used to better understand the collaborative project networks in different markets and for projects of differing sizes. A database was developed based on the collaborative international construction projects where Turkish firms and their non-Turkish partners were involved. A total of 449 projects carried out in 46 countries were used for the analysis. The findings of the study suggest that contractors adopt different strategies depending on the market and project characteristics. The majority of the companies tend to remain in the same markets; they keep working with the same partners or choose local partners; and engage with multiple partners in more complex projects. This study is expected to help contractors reflect on their internationalization decisions and devise appropriate strategies to establish project networks. First published online: 27 Jun 2016